PO81 | Direct oral anticoagulants in atypical site vein thrombosis: a single centre experience focused on cancer patients (Bleeding, Thrombosis and Vascular Biology)
Background and Aims: Atypical sites venous thromboembolism (VTE-AL) is a rare disease has an incidence of 4% in the general population with an involvement of organ-related venous districts such as portal, mesenteric, hepatic, splenic, gonadal, renal, and cerebral venous segments. The risk of VTE in patients with cancer is increased by 12-fold compared with the general population. Major clinical trials on direct oral anticoagulants (DOACS) have excluded patients with VTE-AL. We aimed to evaluate the safety and efficacy of anti-Xa DOACs in our cancer patients with VTE-AL referred to our Centre for congenital bleeding and thrombotic disorders. Methods: We evaluated 7 cancer patients with VTE-AL (3 female and 4 male, median age 65,71 years) referred to our centre since April 2023 till March 2025: 3 (42.3%) with splenoportal axis thrombosis, 2 (28.5%) with inferior vena cava thrombosis, 1 (14%) renal thrombosis. 2/4 patients (45%) had oncohematological desease (Multiple Myeloma, Non-Hodgkin Lymphoma) and 5 patients (55%) had solid cancer (Renal Cancer, Ascending Colon Adenocarcinoma, Sigma Adenocarcinoma, Pulmonary Adenocarcinoma). All patients were diagnosed with received DOACs at full or reduced doses according to the reduction criteria in the drug label.